Prenatal diagnosis and molecular cytogenetic characterization of a pure ring chromosome 21 with a 4.657-Mb 21q22.3 deletion - Chih-Ping Chen; Liang-Kai Wang; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Fang-Tzu Wu; Yun-Yi Chen; Dai-Dyi Town; Wayseen Wang (Taiwanese Journal of Obstetrics & Gynecology, 2021)
Objective: We present diagnosis and molecular cytogenetic characterization of a pure ring chromosome [r(21)] with a 4.657-Mb 21q22.3 deletion. Case report: A 44-year-old woman underwent amniocentesis at 18 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype 46,XX,r(21)(p11.2q22.3). Prenatal ultrasound findings were unremarkable. Simultaneous array comparative genomic hybridization (aCGH) analysis on uncultured amniocytes revealed a 4.657-Mb deletion at 21q22.3. The parental karyotypes were normal. The pregnancy was subsequently terminated, and a malformed fetus was delivered with facial dysmorphism and clinodactyly. Postnatal cytogenetic analysis of umbilical cord revealed a karyotype of 46,XX,r(21)(p11.2q22.3). aCGH analysis of umbilical cord revealed the result of arr 21q22.3 (43,427,188–48,084,156) × 1.0 with a 4.657-Mb 21q22.3 deletion encompassing 57 Online Mendelian Inheritance in Man (OMIM) genes including TRPM2, TSPEAR, COL18A1, COL6A1, COL6A2, LSS, PCNT, DIP2A, S100B and PRMT2. Metaphase fluorescence in situ hybridization (FISH) analysis of the umbilical cord fibroblasts confirmed a 21q22.3 deletion. Conclusion: Prenatal diagnosis of an r(21) should include molecular cytogenetic characterization such as aCGH and FISH to determine the extent of the 21q22.3 deletion.